New York Paper - Some Peculiar Results in Hardness Tests of Lead-antimony Alloys (with Discussion) - L. O. Howard (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
Much work has been done recently on the lead-antimony system1 in connection with lead-rich alloys of commercial importance containing less than 20 per cent. antimony. Dean, Zickrick and Nix have called attention to the perpetuation in the literature of several erroneous data, such as a eutectic temperature of 228° C. at 12.5 per cent. antimony, instead of 247° at 13 per cent. The series is given as a classic example of a straight eutectiferous series in such late books as those of Heyn and Grossmann, 2 Jeffries and Archer,3 Guillet and Portevin,4 Pulsifer,5 Rosenhain,6 and Liddell,' as well as the somewhat earlier works of Hof-man (1918), Wang (1909), and Williams (1920). The work of Dean has definitely shown a solid solution of antimony in lead at about 2.5 per cent. antimony. While lecturing to a class in general metallurgy at the University of Idaho, the writer had the students prepare a series of lead-antimony alloys for the purpose of illustrating methods of thermal analysis. Proper proportions of powdered antimony (sold as C.P.) and test lead were mixed and melted in graphite crucibles under a reducing cover. Cooling